The equation of the line is given as,
![y=2x+2](https://img.qammunity.org/2023/formulas/mathematics/high-school/55a66me1fmp1rnhy3x5pu8v1e3wh5u5gdh.png)
According to the slope-intercept form, the equation of a line with slope 'm' and y-intercept 'c', is given by,
![y=mx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/r9wr7tk2q8cfcans6j0owflua8au85op0h.png)
Comparing with the given equation, the slope of the given line is,
![m=2](https://img.qammunity.org/2023/formulas/mathematics/college/5ybbsqblz53zxngquf5jbxqzfmbd6dyow3.png)
Theorem: The product of two slopes of two perpendicular lines is -1 always.
Let the slope of the perpendicular line be (m'), and 'b' be the y-intercept. Then, it follows that,
![\begin{gathered} m^(\prime)\cdot m=-1 \\ m^(\prime)\cdot(2)=-1 \\ m^(\prime)=(-1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/rrjvnj4a6pj786qaokzlvlki5w548807se.png)
The equation of this perpendicular line is given by,
![\begin{gathered} y=m^(\prime)x+b^(\prime) \\ y=((-1)/(2))x+b^(\prime) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ee43c318svya9q4d8x56ppclb1wkhunnm0.png)
Given that the perpendicular lines pass through the point (6,-2), so it must also satisfy its equation,
![\begin{gathered} -2=((-1)/(2))(6)+b^(\prime) \\ -2=-3+b^(\prime) \\ b^(\prime)=-2+3 \\ b^(\prime)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ehdk77zmb8lknh9jb6cvh6c6g9trr6q90n.png)
Substitute this value back in the equation of the perpendicular line,
![y=(-1)/(2)x+1](https://img.qammunity.org/2023/formulas/mathematics/high-school/f65nwjpihd0yiryqzsaqoxwpxt4zhqjfph.png)
Thus, the equation of a line perpendicular to the given line and passing through the given point is obtained as,
![y=(-1)/(2)x+1](https://img.qammunity.org/2023/formulas/mathematics/high-school/f65nwjpihd0yiryqzsaqoxwpxt4zhqjfph.png)